Hukum OKUN: Pertumbuhan Ekonomi dan Tingkat Pengangguran di Indonesia - Mayra Astari; Lies Maria Hamzah; Arivina Ratih (Jurnal Ekonomi Pembangunan, 2019)
This study examined the validity of Okun's Law on the Indonesian economy by using the difference version of Okun's Law to obtain the Okun coefficient. This study uses the analysis of the Autoregressive Distributed Lag Model (ARDL). The estimation results concluded that Okun's Law proved to have a negative and significant effect on the Indonesian economy because the variable economic growth was shown to influence the unemployment variable statistically.